Design and psychometric validation of the research competency scale for university students in Peru - Luperdi-Román, Carmen Julia de los Milagros; Goñi-Cruz, Félix Fernando; Deroncele-Acosta, Angel (Institute of Advanced Engineering and Science, 2025)
Research competence is essential for the academic and professional development of university students. However, in the context of Lima, Peru, no specific, valid, and reliable instruments have been found to assess this competency comprehensively. This deficiency reveals a significant knowledge gap in the accurate assessment of research competencies in university students. Therefore, in the present research, a scale was constructed and validated to effectively assess research competence in university students. As methodology, the quantitative approach was used, following three processes: item construction, item functionality, and psychometric analysis. A sample of 216 students was used for the exploratory factor analysis (EFA), and 206 for the confirmatory factor analysis (CFA). The final version of the research competency scale for university students comprises 37 items distributed across five dimensions identified through EFA: epistemic knowledge (10 items), interpretation skills (5 items), methodological knowledge (9 items), scientific communication (6 items), and information management (7 items). CFA supported the adequacy of the model (root mean square error of approximation/RMSEA=0.064; comparative fit index/CFI=0.918; Tucker-Lewis Index/TLI=0.911), and the scale demonstrated high internal consistency. The validated scale reliably measures research competence and can improve teaching, assessment, and curriculum design.